Youth entrepreneurship during COVID-19 pandemic: does the government care? / Azyyati Anuar and Daing Maruak Sadek - Anuar, Azyyati; Sadek, Daing Maruak (Faculty of Business and Management, Universiti Teknologi MARA Cawangan Kedah, 2022)
The coronavirus (COVID-19) outbreak has affected people's health and caused a massive impact on businesses among entrepreneurs not only in Malaysia but also around the world. The majority believe that this unprecedented situation will lead to the closure of many firms. Policy mandates, downward demand movements, health concerns, and other issues have forced stores, factories, and many other companies to close (Fairlie, 2020). This can be proven in March 2020, shortly after the Prime Minister of Malaysia announced the Movement Control Order (MCO), a total of 32,465 Small and Medium Enterprises (SMEs) folded due to the proliferation of COVID-19 (Tan et al., 2020). In fact, August set a new high for SME closures with 17,800 SMEs (Free Malaysia, 2020). The former Minister of Entrepreneurial Development and Cooperatives, Wan Junaidi Tuanku Jaafar, reported that a total of 9,675 SME operations ceased during the first phase of the MCO from March 18 to June 9, and 22,794 during the Recovery Movement Control Order (RMCO) phase in June to September (Free Malaysia, 2020). This figure is seen as exorbitant since SMEs are the backbone of the national economy.